Enhancement of Nutritional Profiles in Plant-Based Yoghurt through Lactic Acid Bacteria Fermentation - Gbabo, Ayibabrakemi; Ogunbanwo, Samuel Temitope (PSM Microbiology, 2025)
Yoghurt is widely consumed as a healthy, nutrient-rich food across many cultures. However, dairy intolerance and the growing interest in sustainable diets have driven a significant increase in demand for plant-based alternatives. Fermentation with lactic acid bacteria (LAB) presents a promising approach to enhancing the nutritional and sensory qualities of non-dairy yoghurts. This study aimed to identify suitable LAB strains with desirable fermentative properties to improve the nutritional profile of soy-based yoghurt. LAB strains were isolated from traditional fermented foods, including ogi, wara, and yoghurt, using standard microbiological methods. A total of forty isolates were identified as Lactiplantibacillus plantarum (11), Lactococcus lactis (3), Lactobacillus acidophilus (16), and Limosilactobacillus fermentum (10). Based on probiotic potential, Lb. fermentum and Lb. plantarum were selected as starters, individually and in combination, for soymilk fermentation, with spontaneous fermentation as the control. Fermentation was carried out in heat-treated soybean extract, producing yoghurt-like products with characteristic acidity, creamy aroma, and mustard-like texture. Nutritional analysis revealed that starter-produced soymilk yoghurt contained higher protein and carbohydrate levels, lower fat, and increased fibre compared to spontaneously fermented soymilk. The protein content was slightly lower than that of cow milk yoghurt, while the fat content was significantly reduced. Fibre levels in starter-produced and spontaneously fermented soymilk were comparable. The starter-based product exhibited superior carbohydrate content and the highest overall sensory acceptability. These findings highlight the potential of selected LAB strains to produce nutritionally improved and more acceptable plant-based yoghurts. This study demonstrates that LAB fermentation can enhance the quality of soy-based yoghurt, providing a viable non-dairy alternative for consumers.